Optimizing Zakat and Cash Waqf for Educated Unemployment: Evidence from Sampang Regency: Optimalisasi Zakat dan Wakaf Tunai untuk Pengangguran Terdidik: Bukti Empiris dari Kabupaten Sampang - Wahyu Nur Alfiyan; Surotul Lubna (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study investigates the optimization of productive zakat and cash waqf as strategic instruments to address educated unemployment in rural Indonesia, with a case study of Sampang Regency. The research is motivated by persistent labor market challenges, notably the structural mismatch between secondary education output and job absorption, alongside the dominance of informal employment. Using a descriptive quantitative design based on 2024 National Labor Force Survey data, the study analyzes educational attainment, sectoral employment, and labor status to identify high-priority target groups. Findings show that unemployment peaks among junior and senior secondary school graduates, while informal work dominates 76.6% of employment, with agriculture as the leading sector. A simulation illustrates that Rp2 billion in zakat allocation could empower 1,000 unemployed youths through microenterprise financing and skills training. The discussion anchors this strategy within maqāṣid al-sharīʿah, emphasizing protection of wealth, intellect, and livelihood. The study concludes that integrating Islamic social finance into local labor policies offers both economic and ethical pathways to reduce structural unemployment, provided strong governance and institutional collaboration are in place. This paper contributes a novel framework by linking empirical labor data with Islamic economic values and recommends further research incorporating institutional financial records and beneficiary perspectives.